Speaking Out for Science and Democracy - Knobel , Marcelo; Mohamedbhai, Goolam (International Higher Education, 2022)
In the face of the great challenges that humanity is facing, including the current wave of denialism and autocracy, university leaders appear to be silent. Yet, universities are vital for addressing these challenges and university leaders must show the way forward within their institutions and in society in responding to scientific and environmental misinformation. More than ever, university leaders need to speak out and cannot afford to be complacent.